King St Ladislas, chronicles, legends and miracles - Veszpremy, Laszlo (Saeculum Christianum. Pismo Historyczne, 2019)
Much can be read in the Hungarian chronicle versions and Latin legends about the figure of King St Ladislas (reigned 1077–1095, canonized 1192), the most popular saint in Hungary by the middle of the fourteenth century. These sources are all enlarged and interpolated representation of the elements of the surviving nomad traditions, the chivalric ideas of the Hungarian royal court, elements of the French crusader traditions of the Angevin court, the memory of the struggle against the Mongols in 1241–42. This paper focuses on some of these motifs, like becoming a fictive leader of the First crusade, and a fictive successor to the imperial throne. The paper confronts the textual differences between the legends and the chronicles and tries to answer the question why the hagiographic and liturgical texts neglect his fights against the heathen.